2018
DOI: 10.1155/2018/3852196
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Double‐Blind Placebo‐Controlled Trial to Evaluate Prophylactic Effect of Traditional Chinese Medicine Supplementing Qi and Hemostasis Formula on Gastrointestinal Bleeding after Percutaneous Coronary Intervention in Patients at High Risks

Abstract: Objective To evaluate the clinical efficacy of traditional Chinese medicine (TCM) supplementing Qi and hemostasis formula on gastrointestinal (GI) bleeding after percutaneous coronary intervention (PCI) and thus find out the optimal therapeutic regimen to reduce incidence of GI bleeding without increase of major adverse cardiovascular events (MACEs). Methods In the randomized, double-blinded, controlled trial, 117 participants who underwent PCI were enrolled and evenly distributed into treatment arm (59) and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
(11 reference statements)
0
4
0
Order By: Relevance
“…Existing studies found that TCM invigorating qi and hemostasis helped to reduce the incidence of gastrointestinal bleeding in high-risk groups while inhibiting platelet aggregation. 10 The gastric mucosal protection effect of TCM invigorating qi and hemostasis may be related to the regulation of gastric mucosal protective hormones. Additionally, MTL and GAS are crucial gastrointestinal hormones.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing studies found that TCM invigorating qi and hemostasis helped to reduce the incidence of gastrointestinal bleeding in high-risk groups while inhibiting platelet aggregation. 10 The gastric mucosal protection effect of TCM invigorating qi and hemostasis may be related to the regulation of gastric mucosal protective hormones. Additionally, MTL and GAS are crucial gastrointestinal hormones.…”
Section: Discussionmentioning
confidence: 99%
“…The TCM prescription of tonifying qi and achieving hemostasis has been established for this pathogenesis and primarily comprises Astragalus membranaceus, Radix Pseudostellaria heterophylla root, rhubarb charcoal, Baihe powder, cuttlefish bone, and Panax notoginseng . A randomized controlled study 10 found that the Chinese herbal ingredients of yiqi and hemostasis had some preventive effect on gastrointestinal bleeding after PCI, while the results of a thromboelastic diagram suggested that intervention using Chinese herbal medicine in this context as a result of clopidogrel’s antiplatelet effect was less likely compared with using pantoprazole. Pharmacological studies 8 , 9 suggest that the main components of Chinese herbal medicine for replenishing qi and achieving hemostasis can interfere with gastric mucosal injury, and concurrently, effect a degree of influence on platelet activation.…”
Section: Introductionmentioning
confidence: 99%
“…Further studies confirmed the inhibitory effect of Panax notoginseng saponins on the activity of platelet COX-1 and the downregulation of TXB2, PGD2, and PGE2 expressions [ 67 ]. A randomized controlled study of 117 patients with gastrointestinal bleeding after percutaneous coronary intervention has also shown that the protective effect of traditional Chinese medicines on the gastric mucosa is equivalent to that of pantoprazole sodium enteric-coated capsules [ 69 ]. Overall, PBCRBSCMs can regulate inflammation pathways and AA/COX/PG pathways, exert a protective effect on gastric mucosal epithelial cells, inhibit the occurrence of ulcers, and reduce gastric mucosal damage induced by conventional antiplatelet drugs.…”
Section: The Mechanisms Underlying the Combined Application Of Pbcrbscm And Antiplatelet Drugsmentioning
confidence: 99%
“…But overall, DFD works, which is encouraging. TSS is widely used in TCM clinical research (33,34). We innovatively applied TSS to this study, which was not found in other related studies (26,27,30,31).…”
mentioning
confidence: 96%